Reflections of Turkish traditions of the Northern Black Sea area at the times of Art Noveau - Kotsuibanska, Olga; Levitska, Nadiia (My University, 2018)
The paper dedicated to the theme of Eastern influence to the Ukrainian Black Sea coast on the verge of the 20th century, underlined in the wrappers of Eastern sweets.Стаття, присвячена темі східного впливу на українське узбережжя Чорного моря на межі ХХ століття, підкреслюється в обгортках східних солодощів.
Keywords: department of humanitarian disciplines; wrapper; oriental; sweets; обгортка; східний; солодощі; кафедра гуманітарних дисциплін